(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This article reviews the speed of development among 10-11 years old children playing international soccer in additional education facilities problem. Since these facilities are paying much attention to the technical and tactical part of the game during the training process, there is not much time to develop the qualities that players need. Due to this fact, it is imperative to implement some exercises that help develop young players’ speed in the training course. The goal is to develop the complex of exercises to increase children’s 10-11 years old’s speed using coordination development means. The main approach of the soccer referees training research is structural analysis. The research methods are scientific and methodological literature and information environment on speed development based on coordination development means analysis and generalization, pedagogical surveillance, pedagogical experiment, and mathematical data processing methods. The results of the pedagogical experiment with control and experimental groups comparing in different speed development tests are shown. Speed improving training exercises complexes are developed, including no item exercises, ladder exercises, ball exercises. The results are genuine, proven by Student’s t-test statistic method. This article can be useful for beginner and skilled soccer coaches to implement different exercises in their training process to make the training process more exciting for their trainees and create favorable conditions for speed development.